COMPARATIVE LEGAL ANALYSIS OF ADVOCACY ACTIVITIES IN UKRAINE AND THE LEADING COUNTRIES OF EUROPE - Cherevatiuk, Victoria; Soroka, Daryana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the research is a comparative analysis of the organizational and legal foundations of the functioning of the advocacy in the leading countries of Europe and in Ukraine in order to clarify the possibilities of implementing positive experience during the reform of the institute of the national advocacy. Research methods: to achieve the specified goal, general and special scientific (special) methods were used. The research uses a comparative legal method, which is rightly considered one of the most important scientific means of studying advocacy, especially in the context of studying and using European legal experience at the current stage of the reform of the advocacy. Results: the study of the advocacy in European countries made it possible to identify similarities and differences in the organization and functioning of the institute of the advocacy, as well as the influence of historical, social and legal factors on the formation of modern advocacy systems. In this context, special attention is paid to the analysis of such aspects as the structure of the advocacy, the requirements for the profession of a lawyer, the principles of the independence of the advocacy, as well as its role in protecting the rights of citizens. Discussion: the advocacy is one of the key institutions of the legal system, which ensures the protection of the rights and freedoms of citizens, promotes the implementation of justice and the rule of law. In Ukraine, the institute of advocacy has undergone a significant transformation, which is part of the general process of reforming the legal system. However, in order to fully understand the prospects for its development and increase its effectiveness, it is necessary to refer to a comparative legal analysis of advocacy in countries with developed legal systems, in particular in Great Britain, Germany, France and Poland. For Ukraine, which is in the process of European integration reforms, it is important to take into account the experience of lawyers in European countries and its possible implementation in the practice of law. Ukraine, like other states, has its own peculiarities in the practice of law, determined by national legislation, the level of development of democracy, the peculiarities of the judicial system and state authorities. To improve the prospects for the development of the institute of advocacy in Ukraine, it is important to study international documents and the experience of other countries.